Kedudukan Mahkamah Konstitusi dalam sistem ketatanegaraan Indonesia pasca amandemen UUD 1945 - Al Imdad, Mokhammad Aqil (Maliki Interdisciplinary Journal, 2026)
The Constitutional Court (MK) was established through Article 24C of the 1945 Constitution, representing one of the most consequential structural changes produced by the 1999-2002 constitutional amendments. The institution was consolidated through Law No. 24 of 2003 as an independent judicial body, equal in standing to the Supreme Court, with a specific mandate as guardian and interpreter of the constitution. This article examines the constitutional position of the Constitutional Court in Indonesia’s post-amendment state administration system, covering its foundational basis, detailed jurisdiction, and practical obstacles still encountered. The research employs a normative method using primary legal materials comprising relevant legislation and Constitutional Court decisions. Findings indicate that over more than two decades of existence, the Court has played a concrete role primarily through judicial review; however, three structural problems remain unresolved: the absence of an adequate mechanism for enforcing decisions, an ongoing debate over the boundaries of interpretive authority, and institutional integrity challenges that cannot be addressed solely through procedural reform.